Maslow’s and Beauvoir’s Theories Portrayed on Sarah’s Character - Rahmajati, Viona Edgar; Widyaningrum, Agnes (Humanitatis : Journal of Language and Literature, 2024)
The purpose of this research is to analyze the portrayal of feminine slavery in "Redeeming Love," focusing onunderstanding the underlying motivations and social pressures that lead Sarah to prostitution. This study exploresthe social phenomena of women being enslaved as prostitutes and the motivations behind their choices, using themovie "Redeeming Love." The study follows a descriptive qualitative method to examine Sarah’s depiction as afeminine slave and her motivations by employing a context-oriented approach. The research utilizes Simone deBeauvoir’s theory of feminine slavery and Maslow’s Hierarchy of Needs to analyze the experiences of the maincharacter, Sarah. The research process involved several steps: first, closely observing the movie; second, focusingon Sarah’s dialogue and actions to discern her depiction and motivations; third, selecting and interpreting dialoguesthat reflect the concept of feminine slavery and her reasons for engaging in prostitution. The findings revealthat Sarah’s experiences as a prostitute include both external and internal struggles, which align with Beauvoir’stheory of women’s objectification and devaluation by a patriarchal society. The external experience is how Sarahexperiences feminine slavery from societal views. The internal experience reflects how Sarah experiences feminineslavery from her personal views. Additionally, the study shows that Sarah, as the main female character, experiencessome unfulfilled needs that push her into prostitution. Sarah’s unfulfilled needs are physiological, psychological,esteem, and love-belonging needs. Her unfulfilled needs are caused by her illegitimate status as a child, herfather’s abandonment, her poverty, and her inability to meet basic needs due to combined unfulfilled needs. Theseunfulfilled needs caused her to live as a prostitute. In conclusion, this study provides new insights into the factorscontributing to female enslavement and the needs of women in a patriarchal society, enhancing our understandingof the intersection between women’s objectification and their basic and psychological needs.The purpose of this research is to analyze the portrayal of feminine slavery in "Redeeming Love," focusing onunderstanding the underlying motivations and social pressures that lead Sarah to prostitution. This study exploresthe social phenomena of women being enslaved as prostitutes and the motivations behind their choices, using themovie "Redeeming Love." The study follows a descriptive qualitative method to examine Sarah’s depiction as afeminine slave and her motivations by employing a context-oriented approach. The research utilizes Simone deBeauvoir’s theory of feminine slavery and Maslow’s Hierarchy of Needs to analyze the experiences of the maincharacter, Sarah. The research process involved several steps: first, closely observing the movie; second, focusingon Sarah’s dialogue and actions to discern her depiction and motivations; third, selecting and interpreting dialoguesthat reflect the concept of feminine slavery and her reasons for engaging in prostitution. The findings revealthat Sarah’s experiences as a prostitute include both external and internal struggles, which align with Beauvoir’stheory of women’s objectification and devaluation by a patriarchal society. The external experience is how Sarahexperiences feminine slavery from societal views. The internal experience reflects how Sarah experiences feminineslavery from her personal views. Additionally, the study shows that Sarah, as the main female character, experiencessome unfulfilled needs that push her into prostitution. Sarah’s unfulfilled needs are physiological, psychological,esteem, and love-belonging needs. Her unfulfilled needs are caused by her illegitimate status as a child, herfather’s abandonment, her poverty, and her inability to meet basic needs due to combined unfulfilled needs. Theseunfulfilled needs caused her to live as a prostitute. In conclusion, this study provides new insights into the factorscontributing to female enslavement and the needs of women in a patriarchal society, enhancing our understandingof the intersection between women’s objectification and their basic and psychological needs.